2000
DOI: 10.1038/oby.2000.59
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Insulinotropic Action of Arachidonic Acid through the Lipoxygenase Pathway in the Obese Zucker Rat

Abstract: Objective: The metabolism of arachidonic acid (AA) has been shown to be altered in severe insulin resistance that is present in obese (fa/fa) Zucker rats. We examined the effects and mechanism of action of AA on basal and glucose‐stimulated insulin secretion in pancreatic islets isolated from obese (fa/fa) Zucker rats and their homozygous lean (Fa/Fa) littermates. Research Methods and Procedures: Islets were isolated from 10‐ to 12‐week‐old rats and incubated for 45 minutes in glucose concentrations ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…12LO expression has been shown to be upregulated in islets and beta cells by the proinflammatory cytokine IL-1β [18], and metabolic stresses [14,16,17]. Targeted deletion of leucocyte 12LO also yields protection from low-dose STZ-induced diabetes in the mouse [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12LO expression has been shown to be upregulated in islets and beta cells by the proinflammatory cytokine IL-1β [18], and metabolic stresses [14,16,17]. Targeted deletion of leucocyte 12LO also yields protection from low-dose STZ-induced diabetes in the mouse [19].…”
Section: Discussionmentioning
confidence: 99%
“…12LO message expression is induced under hyperglycaemic conditions in rat islets [14] along with cyclooxygenase. In diabetic Zucker Fatty rats, elevated 12LO expression is associated with deficits in insulin secretion and beta cell decompensation [15][16][17]. 12LO message, protein and activity can be induced by the proinflammatory cytokine IL-1β in rat islets and insulin-secreting beta cells [18].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, 12-LOX knockout mice are protected from developing insulin resistance and β-cell destruction when fed a high-fat diet [98]. 12-LOX gene expression and 12-HETE production is upregulated in adipose tissue and islets from the Zucker diabetic rat, linking this pathway to the progression and development of insulin resistance in type 2 diabetes [99, 100]. Moreover, it was shown that rat islets treated with exogenous 11-HETE, 15-HETE, LTB 4 , and LTC 4 all inhibited insulin secretion [92].…”
Section: Lipooxygenase (Lox) Metabolitesmentioning
confidence: 99%
“…1) (17;1719). Thus, it is important to understand the regulatory role of PLA 2 as the products of their hydrolytic activity have been implicated in the regulation of metabolic disorders (14;2022). …”
Section: Phospholipase A2 Superfamilymentioning
confidence: 99%